2007
DOI: 10.1300/j015v29n03_06
|View full text |Cite
|
Sign up to set email alerts
|

An Ecological Approach to Understanding Incarcerated Women's Responses to Abuse

Abstract: Although women are often criticized for not leaving abusive relationships, most abused women actively attempt to protect themselves. This study proposed an ecological model to explain strategic responses to abuse, evaluating factors at four levels: Childhood, Relationship, Individual Impact of Abuse, and Community. Data was retrospectively collected from 85 incarcerated women, a population that is Melanie J. Bliss, PhD, is a licensed clinical psychologist and a senior researcher for disproportionately affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…In particular a fear of the police, the fear of having children removed, the attitudes of services towards ex-prisoners, a perceived lack of acknowledgement of IPV in prison, relationships with other prisoners, and prisons as places of safety and healing were all identified as relevant to help-seeking. While many of these factors have been identified in previous research with justice-involved women (Bliss et al, 2007;O'Neil, 2017;Pritchard et al, 2014;Wilson et al 2017), this study frames these experiences within a model of help-seeking which suggests that women leaving prison who experience IPV must: (1) recognise and define the abusive situation as intolerable;…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In particular a fear of the police, the fear of having children removed, the attitudes of services towards ex-prisoners, a perceived lack of acknowledgement of IPV in prison, relationships with other prisoners, and prisons as places of safety and healing were all identified as relevant to help-seeking. While many of these factors have been identified in previous research with justice-involved women (Bliss et al, 2007;O'Neil, 2017;Pritchard et al, 2014;Wilson et al 2017), this study frames these experiences within a model of help-seeking which suggests that women leaving prison who experience IPV must: (1) recognise and define the abusive situation as intolerable;…”
Section: Discussionmentioning
confidence: 97%
“…In this study we examine the ways in which the dual status of 'survivor' and 'offender' (Pritchard, Jordan, & Jones, 2014) has the potential to create unique barriers to help-seeking. There have been relatively few previous investigations of this topic, although some of the issues facing ex-prisoners that have been identified in previous studies include a fear of police and child welfare services, difficulties accessing formal services because of a criminal record, and the perception that prison is a place of safety from the abuser and a place to access previously unavailable services (Bliss, Cook, & Kaslow, 2007;Pritchard et al, 2014;Wilson et al, 2017).…”
Section: <Insert Figure 1 About Here>mentioning
confidence: 99%
“…Nason-Clark (2004) also found that shelter workers might have trouble challenging victim's beliefs that the abuse is justified. Traditional gender relations and male physical dominance may also dominate in rural areas (Carrington & Scott, 2008), resulting in a patriarchal ideology that discourages women from seeking victim services (Logan et al, 2004) or from leaving the abusive relationship (Bliss et al, 2006). Dunn and Powell (2005) found that the majority of advocates working in rural areas cited "old-fashioned ideologies" as a barrier to service provision.…”
Section: Macrosystem and Exosystem Issues For Rural Victimization Andmentioning
confidence: 99%
“…We formulate and draw on an ecological model of justice and victim service systems’ responses to IPV to frame our analyses, based on earlier conceptualizations that sought to explain and contextualize IPV (Heise, ; Dutton, ) and more recent scholarship that has considered the ecology of women's strategic choices in responding to IPV (Bliss, Cook, & Kaslow, ; Fleury‐Steiner, Bybee, Sullivan, Belknap, & Melton, ). Although our purpose is to analyze advocates’ intervention in IPV rather than offender or victim behaviors, such applications provide useful direction.…”
Section: Introductionmentioning
confidence: 99%
“…offending (e.g., Bliss, Cook, & Kaslow, 2006). The result of this confluence of factors is that a majority of incarcerated women may hold the dual status of abuse survivor and criminal offender (Greenfield & Snell, 1999).…”
mentioning
confidence: 99%